Challenges of HR managers in remote working after post-COVID pandemic - Devi, Roopa (BOHR International Journal of Operations Management Research and Practices, 2023)
This study helps in exploring the changes in the working of the employees from new normal work to remote working due to coronavirus disease 2019 (COVID 19) pandemic, which has made changes in the role of human resource (HR) managers. The qualitative methodology was applied along with an interview technique. This study revealed the impact of COVID pandemic on impacts within the organization, remote working strategies, and technological adaptation. HR managers faced the challenge of employee satisfaction and organization productivity at the same time. The paper discusses about the challenges of HR on remote working and the strategies to overcome these challenges. The study revealed that the employees had to face problems such as communication problems, lack of motivation to employees, family problems, and health issues.